Correlation of Vitiligo Area Scoring Index with the amount of CXCL 10 serum in vitiligo patient - Ardhiah Iswanda Putri, - (Pakistan Association of Dermatologists, 2019)
Introduction Vitiligo is a skin pigmentation disorder, often progressive and familial, characterized by depigmented macules on asymptomatic skin. This disorder is an acquired idiopathic depigmentation disorder, characterized by scaly/ non-scaly white macules resulting from the loss of skin melanocytes. CXCL 10 is one of the 3 CXCR 3 receptor ligands which have chemotaxic effects on various immune system cells. Serum CXCL 10 can be a new biomarker in monitoring disease activity. Methods This is a descriptive cross-sectional study aimed at evaluating serum CXCL 10 levels in vitiligo patients conducted at Dr. Soetomo general hospital Surabaya, 16 blood samples of patients diagnosed with vitiligo were taken to patients to measure serum CXCL 10 levels. Results Serum CXCL 10 levels in this study were higher in patients with stable vitiligo lesion activity and had high VASI values statistically, p = 0.000 (p = < 0.05). Conclusion There is positive correlation between VASI score and CXCL 10 serum levels.